Competency Development among Hospitality Graduates in Kenya: Assessing the Influence of Industry Based Learning - Onyuna , Alberta A. (African Journal of Education,Science and Technology (AJEST), 2019)
The quality of Kenya’s graduates continues to pose concerns with various stakeholders raising the red flag. Industry based learning has previously been used successfully to expose trainees to requisite job related experiences. In acknowledging the potential impact of industry based learning, this study assessed the influence of industry-based learning on competency development among hospitality graduates in Kenya. The study adopted the explanatory research design to examine the cause-effect relationships between industry based learning approaches and competency development. Both stratified and simple random sampling techniques were used to sample 210 final year hospitality students. Data were collected using self-administered questionnaire for students. Data were cleaned for missing values and outliers upon which 191 cases were retained for analysis. Multiple regressions were used for data analysis. Among the key findings made were that all the three approaches namely internship, practicum and apprenticeship had positive and significant influences on competency development among hospitality graduates. The study concluded that Kenyan Universities offering hospitality education need to invest heavily on industry-based learning that will not only boost their training status but also expose students to realities of the industry expectations.